Prevalence of Intestinal Parasites under Fingernails of Primary School Children in Zakho, Kurdistan Region - Jameel, Ahmad Y.; Issa, Araz R.; Amidy, Kaveen S.Kh.; Mero, Wijdan M. S.; Sabri, Mohammed A.; Khdihir, Mohammed A. (Science Journal of University of Zakho, 2017)
In this study, 103 fingernails samples were collected (31 female and 72 male) from primary school children aged between 6 to12 years, which lived in Zakho city during the period from March to November, 2015. Each fingernail sample was immersed in normal saline, and subsequently centrifuged for 5 minutes at 2500 rpm. The supernatant was discarded; a few drops of the sediment of each sample were placed on the center of a clean glass slide with a drop of iodine or eosin, and then examined microscopically. The results revealed a total rate of 25.24% of infection with parasites. The recorded parasites with their rates included: eggs of Enterobius vermicularis, Hymenolepis nana, Ascaris lumbricoides and Trichuris trichaura (7.76, 5.82, 2.91 and 0.97 %, respectively) and cysts of Entamoeba histolytica and Giardia lamblia (4.85 and 2.91 %). According to age, the highest percentage of infection occurred in 9 years old children. Regarding the gender, males showed a higher rate of infection than females (17.47 % versus 7.76%, respectively). These results clarify the role of fingernails in the transmission of parasitic infections, which requires continuous cleaning and cutting.